The role of mindfulness in improving quality of life among student-athletes: a pilot mediation study - Johles, Lis; Molander, Peter; Lundqvist, Carolina (Frontiers in Psychology, 2025)
IntroductionThere has been a growing interest in mindfulness research during the past three decades. However, studies investigating the mediating mechanisms of mindfulness on student-athletes and their quality of life (QoL) are sparse. The purpose of this pilot study was to examine if the effects of a brief body scan intervention on QoL among student-athletes would mediate a change in five facets of mindfulness (acting with awareness, describing, non-judgment, non-reactivity, and observing).MethodsSwedish student-athletes (n = 99; 40% female participants) were recruited from six provincial high schools specialized in sports (basketball, k = 5; cross-country skiing, k = 1). The student-athletes were randomized into two arms: a 4-week body scan (intervention group) and a 4-week relaxation (active control group). Participants completed self-reported measures of QoL and mindfulness three times: at baseline; at follow-up, 4 weeks after baseline; and 8 weeks after baseline. A simple mediation analysis was conducted.ResultsResults showed no significant differences between the body scan and relaxation on QoL change (c-path). There were no significant associations between the independent variable (body scan and relaxation) and the mediator Five Facet Mindfulness Questionnaire (FFMQ) (a-path). Results did not demonstrate any significant indirect associations between FFMQ and QoL (b-path) for the five facets of FFMQ. In conclusion, body scans did not have any effect on student-athletes’ QoL.DiscussionThis study provides a first step toward investigating facets of mindfulness and QoL among student-athletes. No direct associations were revealed in this pilot study. Future research should refine mindfulness interventions and explore diverse mindfulness practices to better understand which facets of mindfulness may be helpful for student-athletes’ QoL.